Blunt traumatic injury to the thoracic aorta treated with thoracic endovascular aortic repair: a single-centre 20-year experience. (10th July 2018) - Agostinelli, Andrea; Carino, Davide; Borrello, Bruno; Marcato, Carla; Volpi, Annalisa; Gherli, Tiziano; Nicolini, Francesco
Abstract: OBJECTIVES: Blunt thoracic aortic injury can be treated with thoracic endovascular aortic repair (TEVAR) with excellent short and mid-term outcomes. However, few data are available about the long-term results. Our goal was to report our single-centre, 20-year experience using TEVAR to treat blunt thoracic aortic injury. METHODS: We retrospectively reviewed our institutional database to identify all patients treated with TEVAR for traumatic lesions of the aortic isthmus. We identified 35 patients since 1998. Patients' charts were analysed for preoperative characteristics, intraoperative variables and short-term outcomes. Information about the long-term follow-up was collected by analysing cross-sectional images and via phone calls. Follow-up was 100% complete. Rates of survival and of freedom from aortic redo were estimated using Kaplan–Meier methods. RESULTS: Twenty-nine patients were men (82%). The median age was 42 years (range 22–79 years) and the mean injury severity score was 38 (±13). The endovascular procedure was successfully carried out in all patients. The left subclavian artery was intentionally overstented in 11 patients (31%). Two patients died perioperatively (5.7%). The estimated survival was 92% and 87% at 5 and 10 years, respectively, with no aorta-related deaths. The estimated freedom from aortic redo was 96% and 91% at 5 and 10 years, respectively. CONCLUSIONS: Our data corroborate the excellent results of the endovascular treatment of blunt thoracic aortic injury when follow-up is extended to 20 years. New-generation devices, which are more comfortable and have smaller diameters, may further improve the results of TEVAR in treating traumatic aortic injury. Surveillance with cross-sectional imaging remains mandatory.